Implementasi Roya Objek Hak Tanggungan Online Pasca Berlakunya Permen Agraria Nomor 05 Tahun 2020 Tentang Pelayanan Hak Tanggungan Terintegrasi Secara Elektronik - Nabila, Syadzwina Hindun (KANJOLI Business Law Review, 2024)
Article 1 of Regulations of the Minister of Agriculture and Space Administration/Head of the National Farming Agency No. 05 of 2020 on Electronically Integrated Dependency Services provides the definition of electronic liability services, that is, the stages of the service of liability rights in a network that is organized electronically. There are considerable differences between a conventionally executed and an electronically executed right of claim. One of the differences is the removal of dependence. (roya). This study uses a method of normative juridic approach, with specifications that are analytical descriptive. The data used is secondary data obtained from a library study. The results of this study show that the application for the cancellation of roya liability conventionally should be made directly to the land office with the result of a physical record issued by the land bureau. Conventionally, the right of responsibility is no longer enforced, all of it is transferred to the HT-el system. In the electronic royalty, the party applying for the right to responsibility can apply through the system with the attachment of the specified requirements, and the result is an electronic document.